TOTAL ERITROSIT DAN LEUKOSIT BROILER JANTAN SETELAH PEMBERIAN JINTAN HITAM (Nigella sativa) SEBAGAI IMUNOMODULATOR DALAM AIR MINUM - Hani Maya Sapitri; Purnama Edy Santosa; Sri Suharyati; Muhammad Mirandy Pratama Sirat (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2021)
This research aimed to determine the effectiveness of Nigella sativa on total erythrocytes and leucocytes of male broiler. This research was conducted on December 2019–January 2020 at the Integrated Field Laboratory, Faculty of Agriculture, University of Lampung. Examination of total erythrocytes and leucocytes was conducted at Pramitra Biolab Indonesia clinical Laboratory, Bandar Lampung. The experimental design used was a completely randomized design (CRD) with four treatments and three replication. The treatments given were drinking water without Nigella sativa (P0), drinking water with 36 mg/kg BW/day of Nigella sativa (P1), drinking water with 72 mg/kg BW/day of Nigella sativa (P2), drinking water with 144 mg/kg BW/day of Nigella sativa (P3). The data obtained were analyzed descriptively. The results showed that giving Nigella sativa at a dose of 144 mg/kg BW/day (P3) was an effective dose for increasing total erythrocytes and leucocytes. Keywords: Erythrocytes, Leucocytes, Male broiler, Nigella sativa